Indigenous Australian Image and Text : Mad Bastards 'write life in every stroke' - Polak, Iva (Array, 2014)
Though labelled “Australia’s latest buzz film” receiving glowing reviews at the Sundance Film Festival, Mad Bastards (2010, dir. Brendan Fletcher) is not known to the wider film audience. This is not surprising because the international audience has been missing a series of Australian Indigenous films from the late 1990s onwards that make up what critics growingly referred to as the “Blak Wave”, the most distinct late 20th-century development in Australian national cinema. Set in Western Australia’s Kimberley region, Mad Bastards offers a realistic depiction of the contemporary life in a remote Indigenous community. Uncompromising in the portrayal of violence, yet humorous and humane in the portrayal of Indigenous characters, the film tells a yarn which is, on the one hand, universal – that of the father-son relationship – and, on the other, very local because father-son nexus is arguably the most fragile relationship in Indigenous communities in Australia. The paper argues that the poem “Unreceived Message”, written in prison by the late Indigenous poet Robert Walker (1958-84), shows what happens when the lyrical subject of the poem gets released from prison, and walks into Fletcher’s film some 25 years later as the protagonist in order to rebuild what is left of his pride, identity and fatherhood. It shall be argued that even though violence and abuse as shown in the film can be easily attributed to the long-lasting consequences of colonial disciplining of Indigenous body, the film does not even attempt to contribute to the ongoing debate of blaming others for what is known in Australia as “Indigenous disadvantage”. Rather, it shows how tormented individuals as well as communities can painstakingly heal from within, without the governmental “do-gooders”, thus giving the film an uneasy but realistic closure.